2022
DOI: 10.3390/pharmaceutics14102240
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the Benefit and Risk Data in Between-Drug Comparisons: Illustration of the Challenges Using the Example of Mefenamic Acid versus Ibuprofen

Abstract: Evidence-based pain therapy should rely on precisely defined and personalized criteria. This includes balancing the benefits and risks not only of single drugs but often requires complex between-drug comparisons. Non-steroidal anti-inflammatory drugs (NSAIDs) have been available for several decades and their use is described in an abundance of guidelines. Most of these guidelines recommend that ‘the selection of a particular NSAID should be based on the benefit-risk balance for each patient’. However, head-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
1
2
0
1
Order By: Relevance
“…This study showed that Aspirin, Ibuprofen and Mefenamic Acid were the most commonly used NSAIDs by the patients who enrolled in this study, the prevalence of Aspirin use seems to be mostly due to its anti-platelet effect that inhibits thromboxane A2 and inhibits thrombus formation which is mainly used for cardiovascular diseases rather than as an analgesic, as proven by taking medical history and this use has been confirmed by many clinical studies. 23 The prevalence of using Ibuprofen and mefenamic acid seemed to be directly proportional to their analgesic effect, as most of our cases taking these two drugs had a chief complaint of pain, this is further confirmed by many studies 7,24 , Ibuprofen and mefenamic acid are the most commonly used and most frequently prescribed NSAIDs for their prominent analgesic, anti-inflammatory and antipyretic action. While a study done by Varga et al in 2013 showed that ibuprofen is less frequently prescribed among hospitalized patients compared to other members of NSAIDs.…”
Section: Discussionsupporting
confidence: 61%
“…This study showed that Aspirin, Ibuprofen and Mefenamic Acid were the most commonly used NSAIDs by the patients who enrolled in this study, the prevalence of Aspirin use seems to be mostly due to its anti-platelet effect that inhibits thromboxane A2 and inhibits thrombus formation which is mainly used for cardiovascular diseases rather than as an analgesic, as proven by taking medical history and this use has been confirmed by many clinical studies. 23 The prevalence of using Ibuprofen and mefenamic acid seemed to be directly proportional to their analgesic effect, as most of our cases taking these two drugs had a chief complaint of pain, this is further confirmed by many studies 7,24 , Ibuprofen and mefenamic acid are the most commonly used and most frequently prescribed NSAIDs for their prominent analgesic, anti-inflammatory and antipyretic action. While a study done by Varga et al in 2013 showed that ibuprofen is less frequently prescribed among hospitalized patients compared to other members of NSAIDs.…”
Section: Discussionsupporting
confidence: 61%
“…2 Naproxen, ibuprofen, and celecoxib have the better safety among NSAIDs. 85 However, with respect to the other NSAIDs, ibuprofen shows an interesting pharmacokinetic profile: therapeutic concentrations are reached after 30 min, and plasma half-life is approximately 1.8-2.44 h, showing a rapid activity and a rapid clearance, 86 supporting its use in COVID-19 symptomatic management (Tables 1 and 4). In 2271 patients positive for COVID-19, Castro et al showed that ibuprofen and naproxen reduced the rate of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Selama trimester ketiga, asam mefenamat dapat menyebabkan risiko toksisitas kardiopulmonari terhadap fetus, hipertensi pulmonal, gagal ginjal, dan perdarahan intrakranial. Pada akhir masa kehamilan, dapat terjadi perdarahan meskipun dalam dosis kecil asam mefenamat sehingga tidak disarankan untuk dikonsumsi kecuali apabila telah mendapat rekomendasi dari dokter maupun apoteker (Farkouh et al, 2022).…”
Section: Rasionalitas Pengelolaan Obat Pereda Nyeriunclassified